Development of new N -4-[(7-Chloro-5-methylpyrrolo[2,1-f ] [1,2,4]triazin-4-yl)oxy]-3-fluorophenylbenzenesulfonamide analogues: exploring anticancer potential through MerTK inhibition - Sathe, Balaji Dashrath; Meenakshi, Meenakshi; Murti, Yogesh; Mane, Madhav Shivaji; Pandey, Sarvesh Kumar; Mahajan, Shriya; Rawat, Pramod; Kandhari, Harsimrat; Goel, Kapil Kumar; Dwivedi, Ashish Ranjan; Rathod, S. V. (Synlett, 2025)
Mer proto-oncogene tyrosine-protein kinase (MerTK), a part of the TAM (TYRO3, AXL, and MerTK) family, is directly correlated with metastasis and various types of cancers. The inhibition of this receptor is a promising strategy for more-effective chemotherapy. Considering the pharmacophoric features of the active domain of MerTK and the structural characteristics of the investigational drug BMS794833, we designed five new N -{4-[(7-chloro-5-methylpyrrolo[2,1- f ][1,2,4]triazin-4-yl)oxy]-3-fluorophenyl}benzenesulfonamide analogues. In cytotoxicity studies, one of the analogues displayed a significantly higher cytotoxicity than cisplatin. It showed IC50 values of 2.09, 1.96, and 3.08 mu M against A549, MCF-7, and MDA-MB-231 cancer cell lines, respectively. In drug metabolism and pharmacokinetic studies, it was the most stable analogue and displayed a moderate MerTK inhibitory potential. Molecular-docking studies were performed to corroborate the MerTK inhibition, and the same analogue achieved the most significant docking score (-12.33 kcal/mol). Docking interactions demonstrated that the imine and amine group of the 3-chloropyridine moiety of BMS794833 formed hydrogen bonds with the main chain of the ATP pocket residue Met674, while the oxygen atoms of the 4-oxo-1,4-dihydropyridine-3-carboxamide moiety established hydrogen bonds with the Lys619 and Asp741 amino acid residues of the allosteric pocket of MerTK protein. These promising results provide evidence that the N -{4-[(7-chloro-5-methylpyrrolo[2,1- f ][1,2,4]triazin-4-yl)oxy]-3-fluorophenyl}benzenesulfonamide pharmacophore can give potential insights into the development of new MerTK inhibitors.
Keywords: cancer chemotherapeutics; kinase inhibitors; metabolic studies; pyrrolotriazines; sulfonamides